The effect of sizing and surface oxidation on the surface properties and tensile behaviour of recycled carbon fibre: An end-of-life perspective. (November 2020) - He, Di; Soo, Vi Kie; Stojcevski, Filip; Lipiński, Wojciech; Henderson, Luke C.; Compston, Paul; Doolan, Matthew
Highlights: Pyrolysis recycling of carbon fibre (CF) with/without sizing and surface oxidation. Twice the reduction in tensile strength of surface-treated CF versus untreated CF. More significant surface defects in surface-treated CF after recycling. Interaction between sizing agent and functional groups causing fibre degradation. Insights for CF producers and recyclers to reduce the down-cycling of CF. Abstract: Carbon fibre is not widely recycled due to the inconsistent tensile properties of the recycled carbon fibre (rCF). It is unclear whether the surface treatments for virgin carbon fibre (vCF) have an impact on the quality of rCF. This paper presents an experimental investigation into the effect of epoxy sizing and electrochemical oxidation for vCF on the tensile and surface properties of rCF recycled by pyrolysis. Carbon fibre with sizing, or surface oxidation, or both, experience a reduction in tensile strength by 44.6%, 43.7% and 50.1%, respectively, during the recycling process, compared to 19.8% for un-treated fibre. Surface-treated carbon fibres exhibit more surface defects ( ID /IG from 1.6 to 2.7 from Raman spectroscopy) and a smaller average crystallite size (from 7.6 nm to 6.2 nm from X-ray diffraction) after recycling. The results indicate that the interactions between the sizing agent and surface functional groups contribute to the down-cycling of carbon fibre.